The marketing mix of banking services and its impact on achieving sustainable customer value: بحث تحليلي لآراء عينة من الموظفين في مصرف الرافدين /فرع العباس 375 - عادل عباس الجنابي; محمد سعيد ماصخ (Iraqi Journal for Administrative Sciences, 2024)
This research seeks to determine the relationship between the marketing mix of banking services and the achievement of the value of a sustainable customer. In order to achieve this, the elements of the marketing mix of banking (price, service, distribution, promotion, individuals, operations, physical evidence) were adopted. (Captali, 2006) Al-Rafidain Bank, Al-Abbas Branch, has selected 375 research fields through a questionnaire of 50 heads of departments, units and divisions. The weighted arithmetic mean, standard deviation, correlation analysis, and regression analysis were used. Watt reached a set of conclusions, concluded the research with a number of appropriate suggestions.